Anselmo Fletes Bolaños and his position against the creation of The Nicaraguan Academy of the Language: Analysis of the letters and press articles sent to RAE’S secretary - Martín Cuadrado , Carmen (2025)
This article analyses the role played by the Nicaraguan Anselmo Fletes Bolaños in the process of creating the Academia Nicaragüense de la Lengua, founded in 1928. After describing the post-independence context in which the various Corresponding Academies began to take shape, we focused on the letters that Fletes Bolaños sent to the secretary of the RAE. In addition, we study the press clippings that Fletes Bolaños included with the letters, which help us to understand the opposing judgements that the intellectual makes about the members of the Nicaraguan Academy. Finally, the historiographical documents studied are given value, as they are essential materials for further research into Nicaraguan Spanish from a diachronic perspective. With the above, the aim is to see how Fletes Bolaños' contributions have a relevant impact on the future of the Nicaraguan institution.